Unveiling Factors Related to HB0 Immunization Services in Infants - Rosmadewi Rosmadewi; Monica Dara Delia Suja; Rizki Wulandari (Poltekkes Kemenkes Tanjung Karang, 2026)
HB0 immunization is a hepatitis vaccine given to newborns within 24 hours after birth to prevent transmission of the hepatitis B virus. The provision of HB0 immunization is still far below the target. In South Lampung Regency in 2023, the lowest HB0 immunization coverage was at Talang Jawa Public Health Center at 87.7%, while the target was 100%. Several factors, including maternal knowledge, education, attitudes, and family support, may influence this low coverage. This study aimed to determine the factors related to infant health services regarding HB0 immunization. This is a quantitative study with a cross-sectional research design. The population in this study comprised all mothers who had newborn babies in 2024 in Talang Jawa, totaling 145 people across 7 villages, while the sample numbered 113. The sampling technique used was probability sampling, specifically simple random sampling. Univariate analysis used percentages, and bivariate analysis used the Chi-Square test. The results of this study indicate that maternal knowledge (p-value = 0.001), maternal education (p-value = 0.025), maternal attitude (p-value = 0.001), and family support (p-value = 0.001) are significantly related to the provision of Hb0 immunization. Providing counseling to pregnant women and involving cadres to encourage them to come to the health facility to learn about the importance of HB0 immunization; they understand that their babies must be immunized against HB0 to avoid transmission of Hepatitis B.